Assessing the Clinical Utility of the Early Postoperative Pharyngogram in Hypopharyngeal Surgery for Dysphagia. (10th May 2021) - Gobillot, Theodore A.; Garber, David; Merati, Albert L.; Wandell, Grace M.
Abstract : Objectives/Hypothesis: To evaluate the clinical utility of postoperative contrast x‐ray pharyngograms (XRP) for detecting pharyngoesophageal leaks following hypopharyngeal dysphagia surgery. Study Design: Retrospective cohort study. Methods: Medical records were reviewed of patients undergoing endoscopic (E‐) or open (O‐) Zenker's diverticulectomy (‐ZD) with cricopharyngeal myotomy (‐CPM) and CPM alone from 2008 to 2020 at one academic institution. Exclusion criteria were patients who were fed enterally or underwent repair of epiphrenic diverticula or O‐CPM during laryngectomy. XRP clinical indication, impact on clinical care, and factors associated with use patterns were examined using descriptive statistics and logistic regression (LR). Results: Of 152 subjects, 52% underwent O‐ZD, 30% O‐CPM, 15% E‐ZD, and 3% E‐CPM. An XRP was ordered for 65% of subjects, mostly routinely (94%). Among the four clinically apparent leaks observed in this cohort, early postoperative XRP confirmed one. It did not identify any clinically silent leaks. In univariate LR, undergoing XRP was associated with increasing day of diet advancement (odds ratio [OR] 4.7, 95% confidence interval [CI] 2.5–10.5) and hospital stay duration (OR 3.2, 95% CI 2.1–5.2), as well as surgeon specialty of otolaryngology compared to general surgery (OR 12.8, 95% CI 4.8–40.8) and procedure sub‐type (O‐CPM: OR 0.03, 95% CI 0.002–0.16). In multivariate LR, the following variables were significantly associated with XRP use: hospital stay (OR 1.7; 95% CI 1.1–3.0), otolaryngology (OR 105; 95% CI 15.4–2193), O‐CPM (OR 0.03; 95% CI 0.002–0.16), and E‐CPM (OR 0.04, 95% CI 0.002–0.60). Conclusions: Prospective, multi‐institutional studies are needed to confirm the low clinical utility we observed of early, postoperative XRP following hypopharyngeal surgery for dysphagia. Level of Evidence: 3 Laryngoscope, 132:272–277, 2022